THE FUTURE AS A SUBJECT OF PHILOSOPHICAL ANALYSIS UNDER CONDITIONS OF ECOLOGICAL CHALLENGES AND SUSTAINABLE DEVELOPMENT IN THE PHILOSOPHICAL CONTEXT - Зінченко, Наталія; Харламов, М.; Штепа, О.; Кривоніс, А. (SWorldJournal, 2026)
The article offers a philosophical analysis of the future as a problematic and multidimensional concept in the context of escalating global ecological challenges. The relevance of the study is determined by the systemic nature of the contemporary environm